Experiences and challenges of the integrated development model on job creation - Rutarindwa, Alphonse; Akena, Francis; Ocan, Johnson (ADPEBI Publisher, 2024)
This study proposes to explore the experiences and challenges of the integrated development program model on job creation in Rwanda’s Gasabo District. The study aims to understand how this model contributes to job opportunities, economic empowerment and community development within the District. In terms of methodology the study adopted a mixed methods approach, the study combined qualitative and quantitative research techniques. Surveys was quantified the extent of job creation, while interviews were explored the perceived social and economic impacts on the local population, including challenges encountered in implementing this model. Results: The results revealed that the implementation of the integrated development model (IDM) in the Gasabo District reveals significant positive outcomes, particularly in healthcare, infrastructure, and financing initiatives for women and youth. High approval ratings were noted for health center establishment (M = 4.90, SD = 0.43) and infrastructure improvements (M = 4.70, SD = 0.71), underscoring their critical roles in economic development. Job creation showed promise, with small-scale business initiation with mean score of 4.66 although challenges in income diversification persisted (Meam = 3.84, St. dev = 1.26). A strong correlation (R = 0.807) was found between various predictors and job creation, with skills development emerging as a significant predictor (B = 0.149, p < .001). The study concluded that Moreover, the R Square value of 0.651 indicates that approximately 65.1% of the variance in job creation can be attributed to Integrated Development Model (IDM) implementation in the Gasabo District. Limitations: the limitations of the study conclude potential biases in self-reported data and the geographical limitation to Gasabo District, which may not fully capture the national context. Contribution: The findings of this study contributed to the understanding of integrated development program models in job creation and provide policy recommendations for enhancing these interventions. By highlighting the role of community-based interventions, this research can provide a scalable model for other districts in Rwanda and beyond. Importantly this research increased insights into how integrated development program models can address unemployment and promote sustainable economic growth.